2018
DOI: 10.1017/s1463423618000348
|View full text |Cite
|
Sign up to set email alerts
|

Integrated perinatal mental health care: a national model of perinatal primary care in vulnerable populations

Abstract: Implementation of a universal screening process for PMADs alongside the development of an IBH model in perinatal care has led to the creation of a program that is feasible and has the capacity to serve as a national model for improving perinatal mental health in vulnerable populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…The University of Colorado integrated model screens all women at intake and during the third trimester. High-risk women are additionally screened 2 weeks postpartum (Lomonaco-Haycraft et al, 2018). Defining screening intervals and identification of patients at high-risk junctures during pregnancy will be important investigations in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The University of Colorado integrated model screens all women at intake and during the third trimester. High-risk women are additionally screened 2 weeks postpartum (Lomonaco-Haycraft et al, 2018). Defining screening intervals and identification of patients at high-risk junctures during pregnancy will be important investigations in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Integrated models that incorporate mental health services into perinatal care are emerging. A major advantage of an integrated model is that patients are four times more likely to follow-up (FU) with mental health services when offered in tandem with obstetric services compared with being treated outside of the obstetric clinic (Judd, Stafford, Gibson, & Ahrens, 2011; Lomonaco-Haycraft et al, 2018; Melville et al, 2014; Poleshuck & Woods, 2014; Sit et al, 2009). A small study in rural Australia ( n = 107) reported successful integration of a mental health clinic within the confines of an obstetric clinic to treat PPD using experienced psychiatric nurses trained in perinatal mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Further, among mothers with subthreshold levels of trauma-related distress, additional prevention efforts targeting avoidance behaviors and bolstering emotional awareness (e.g., mindfulness techniques, in vivo exposure to feared stimuli) may be warranted. Last, given that pregnant women and their partners engage more regularly with the healthcare system, models of integrated perinatal care offer an ideal opportunity for increased screening and intervention efforts (Lomonaco-Haycraft et al, 2019).…”
Section: Theoretical and Empirical Implicationsmentioning
confidence: 99%
“…The World Health Organization's reproductive health programme has made maternal mortality reduction its primary goal [20]. Mental health screening during pregnancy has been endorsed by the American College of Obstetricians and Gynecologists, the United States Preventive Services Task Force, and the American Academy of Pediatrics as a way to improve pregnancy outcomes such as preterm birth and low birth weight, as well as maternal-child health and wellness in the long run [21].…”
Section: Introductionmentioning
confidence: 99%